Saber profissional do professor que ensina aritmética no contexto histórico da instrução pública do Mato Grosso de 1910 a 1930 - LEANDRO DE OLIVEIRA (2024)
The objective of the research of this thesis was to analyze narratives of objectification of professional knowledge of teachers whose works were used to guide the teaching of the fundamental numbers and operations of arithmetic in the context of elementary teacher education in Mato Grosso, between 1910 and 1930. The sources used to achieve this objective bring together a significant number of documents, such as teaching programs, educational legislation, minute books and state government reports, among others, which were collected in the Public Archive of Mato Grosso and in several state public libraries, which made it possible to identify textbooks and pedagogical manuals indicated to guide the practice of teachers from the same state. The methodological procedures adopted correspond to the Heptagonal Scheme, defined in the context of the research group in which the work was carried out. The sources produced were analyzed based on the New Cultural History proposed by Peter Burke, highlighting concepts and historical processes of cultural production of knowledge. It was possible to verify that the knowledge produced, in the considered context, was guided by an attempt at triadic didactic objectification anchored in three complementary epistemological axes, including specific arithmetic knowledge (disciplinary), pedagogical knowledge to guide teaching (didactic), and institutionalized knowledge of pragmatic references (local), which synthesize the two previous knowledge. The synthesis of this knowledge of triadic objectification of teaching and training of teachers who teach mathematics constitutes the knowledge to be taught, to teach, and the local knowledge.